2003
DOI: 10.21273/horttech.13.4.0706
|View full text |Cite
|
Sign up to set email alerts
|

Performance of Chip Processing Potato Varieties in Northeastern Florida

Abstract: Potato (Solanum tuberosum) is a high value crop in Florida. It consistently ranks in the top five valued vegetable crops produced in the state. The identification of new potato varieties that improve production efficiency is an imperative because of constantly evolving market and production demands. A chip potato variety evaluation experiment was conducted in northeast Florida in 2002 to compare the production characteristics of industry standards to advanced selections. The … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
5
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 3 publications
3
5
0
Order By: Relevance
“…Upon accounting for size and external quality parameters of green, growth cracked, misshapen and decayed tubers, each year averaged 14.7, 32.3, and 32.6 Mg ha −1 of marketable tubers, which represented losses of 42, 14, and 12% of total tubers harvested, respectively. Mean marketable yield in 2011 and 2012 were similar to previous reports in northeastern Florida for potato cultivar Atlantic receiving 224 kg ha −1 N (Hutchinson et al, 2003) and slightly higher than average yield of 28 Mg ha −1 reported for the Hastings area (USDA, 2014). Marketable potato yields were similar among N emerg treatments with the only exception being Farm 3 in 2010 where marketable yield increased linearly in response to N emerg (Table 4).…”
Section: Resultssupporting
confidence: 83%
“…Upon accounting for size and external quality parameters of green, growth cracked, misshapen and decayed tubers, each year averaged 14.7, 32.3, and 32.6 Mg ha −1 of marketable tubers, which represented losses of 42, 14, and 12% of total tubers harvested, respectively. Mean marketable yield in 2011 and 2012 were similar to previous reports in northeastern Florida for potato cultivar Atlantic receiving 224 kg ha −1 N (Hutchinson et al, 2003) and slightly higher than average yield of 28 Mg ha −1 reported for the Hastings area (USDA, 2014). Marketable potato yields were similar among N emerg treatments with the only exception being Farm 3 in 2010 where marketable yield increased linearly in response to N emerg (Table 4).…”
Section: Resultssupporting
confidence: 83%
“…ifas.ufl.edu/cv131. Hutchinson et al (2003) and Sisson and Porter (2002). 2001 4 2 8 7 3 5 4 0 0 0 0 2002 4 3 7 7 4 7 5 0 0 0 0 2003 6 3 7 7 4 7 7 0 0 0 0 2004 7 3 7 8 5 8 8 0 0 0 0 2005 8 3 7 6 5 7 6 Table (Table 1).…”
Section: Other Informationmentioning
confidence: 97%
“…2016. Potato Vine Killing or Hutchinson et al (2003) and Sisson and Porter (2002). 1 Marketable yield: Sum of size classes A1 to A3.…”
Section: Other Informationmentioning
confidence: 99%